The organizational change process during COVID-19 pandemic in a public university: The case of Kasetsart University, Thailand - Joefrey B. Geroche; Xiangyi Yang (Northern Negros State College of Science and Technology (NONESCOST), 2022)
This research paper is a qualitative case analysis research that utilizes Kotler's Eight Processes to accelerate change in accessing the experienced of Kasetsart University in terms of organizational change. The study utilized the empirical data from the KU website, memorandum, and announcement about university operations throughout the widespread COVID-19, and the interview was conducted with two key people knowledgeable in this subject. As an outcome, the study found out that KU experienced a digital organization transformation during COVID-19. Furthermore, the KU established the Strategic Plan of Actions during COVID-19 Temporary Closure: Exit Strategies focused on advancing digital innovation as an organizational development initiative. The lesson from the case study is that KU's preparedness, comprehensiveness, and cross-sectoral methodology were essential in successfully implementing change. Kotter's eight-step progression for accelerating the modification model was a valuable means to convey metamorphic modification in implementing digital transformation in the entire KU; thus, it is recommended for future researchers that the study results are the basis of reference in the digital transformation change in higher education. Most importantly, this can be converted in quantitative research wherein one variable construct is digital transformation change.